Effect of increasing tellurium content on the electronic and optical properties of cadmium selenide telluride alloys CdSe1-xTe x: An ab initio study - Ali Hussain, Reshak, Prof. Dr.; Kityk, I. V.; Khenata, R.; Auluck, S. (Elsevier B.V., 2011)
Link to publisher's homepage at http://www.elsevier.com/